Digitization of older Croatian dictionaries: a possible substratum for terminological neologisms? (Libellarium: journal for research in the field of information and related sciences, 2017)
Considering that the present-day Croatian still frequently fails to have the exact translational equivalents for the novel ideas developed and disseminated via metalinguistic Eurospeak, the paper adopts and employs an unorthodox scientific method to refer to an articulated correlation between a conceptual framework theorized (i.e., the noninvasive library digitization projects pertaining to the select Croatian bi- and trilingual lexicography from the 17th to the 20th century) and the hypothetical questions addressed (i.e., their applicability to the coinage of Croatian neologisms that formationally imitate the previous paragons), with a pronounced tendency to signify a progressive replacement of the perplexingly anglicized language registers by the more decipherable formality levels. Consequently, such a succinct analysis results in a revalorization of the computerized conversion efforts and a permanent appraisal of the Croatian thesauri, which are neither antiquated nor obsolescent but may be incentively put into service for further similar studies in the subject matter.
Keywords: Croatian lexicographic heritage; digitization; metalinguistic neologisms (Eurospeak); systematization; terminology